Global research hotspots and trends in anti-inflammatory studies in dry eye: a bibliometric analysis (2004–2024) - Wang, Shan; Zheng, Wei; Li, Ting; Yu, Dongxu; Zhang, Qi; Ju, Yuan; Wei, Lijuan (Frontiers in Medicine, 2024)
Background: Inflammation plays a crucial role in the pathophysiology of dry eye(DE). This study aims to provide a comprehensive overview of the current status, hotspots and trends in DE anti-inflammatory research through bibliometric analysis. Method: All publications were searched using the Web of Science Core Collection (WoSCC) database from 2004 to 2024. Bibliometric analyses were performed using VOSviewer, R-bibliometrix and CiteSpace, and data were managed using Microsoft Office Excel 2019. Results: There were 603 papers published between 2004 and 2024 included in this study, with the number of papers increasing each year. The United States was the major contributor, with the largest number of publications and the greatest impact. Baylor College of Medicine was the most influential research institution. Pflugfelder, Stephen C. and Tsubota, Kazuo were the most prolific authors in this area of research, while Dana, Reza was the most cited author in the field with the highest impact. The Journal with the highest number of publications was Investigative Ophthalmology & Visual Science, while the highest impact journal was Ocular Surface. Research hotspots were focused on the mechanisms of inflammation in DE and interventions for anti-inflammatory therapy. Future studies would favor more inflammation-related targeted therapies and physical therapies. Conclusion: This study is the first bibliometric analysis to comprehensively summarize research trends and developments in DE anti-inflammatory treatments, pointing out recent research frontiers and hot directions for scholars studying DE anti-inflammatory treatments.